Production and characterization of Imperata cylindrica paper using potassium hydroxide as pulping agent (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Madung Z, Soloi S, Majid MHA, Sarjadi MS. 2022. Production and characterization of Imperata cylindrica paper using potassium hydroxide as pulping agent. Biodiversitas 23: 1490-1494. Non-woody plants have become an alternative fiber in paper production as woods, the primary sources of papers have become limited due to increasing demand of paper year by year. Imperata cylindrica or cogon grass as the source of fiber for the pulp and paper industry in replacing the wood fiber because it has high cellulose and low lignin content.  In this study, cogon grasses were treated with various concentrations of potassium hydroxide, KOH (5%, 8%, 10% and 12%). The effects of alkali treatment on the properties of the papers were investigated in the present study. Scanning Electron Microscope (SEM) image of the paper sheet indicates that the amount of cellulose fiber and other materials were lessening toward a higher concentration of KOH treatment. This explained that most of the lignin was entirely removed and some cellulose probably degraded at higher KOH concentrations. Fourier Transform Infa-Red (FTIR) analysis showed that the peaks at range 1650 cm-1-1630 cm-1 attributed to the presence of v(C=C) aromatic ring of lignin disappeared at 10% and 12% of KOH. The mechanical strength of the papers decreased with an increasing concentration of KOH, while 5% of KOH produced the highest value of tensile strength.
Keywords: imperata cylindrica; non woody plant; surface morphology; potassium hydroxide pulping